Program Sehat Tanpa Napza untuk Meningkatkan Drug Use Resistance Self Efficacy: Prevensi Primer Penyalahgunaan Napza pada Remaja - Hasan Fahrur Rozi; Maria Goretti Adiyanti (Faculty of Psychology, Universitas Gadjah Mada, 2019)
This research aimed to assess the influence of program sehat tanpa napza on drug use resistance self-efficacy. Quasi-experiment (untreated control group design with dependent pretest and posttest) was used as the design of the study. The participants of this study were eight-grader students from two junior high schools in Yogyakarta, which X junior high school was the experimental group and Y junior high school was the control group. Drug use resistance self-efficacy was measured with drug use resistance self-efficacy scale modified from Carpenter (2006). The data were analyzed with ANOVA mixed design using SPSS. The result shows that Program Sehat Tanpa Napza was not significantly increased drug use resistance self-efficacy in an experimental group of adolescent compared with the control group (F = 1.056; p > 0.05). However, adolescent’s drug use resistance self-efficacy in the experimental group was increased significantly.